2015
DOI: 10.1016/j.tranon.2015.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Nuclear Orientation Patterns of Chromosome 11 during Mouse Plasmacytoma Development

Abstract: Studying changes in nuclear architecture is a unique approach toward the understanding of nuclear remodeling during tumor development. One aspect of nuclear architecture is the orientation of chromosomes in the three-dimensional nuclear space. We studied mouse chromosome 11 in lymphocytes of [T38HxBALB/c]N mice with a reciprocal translocation between chromosome X and 11 (T38HT(X;11)) exhibiting a long chromosome T(11;X) and a short chromosome T(X;11) and in fast-onset plasmacytomas (PCTs) induced in the same s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The nuclear architecture of cancer cell nuclei is unique. These nuclei undergo dynamic structural aberrations that include changes in their 3D organization of telomeres, chromosomes and chromosome orientation (Mai, ; Gadji et al, ; Righolt et al, ; Martin et al, ; Schmälter et al, ). This study demonstrates that the tumor cell‐specific 3D nuclear telomere organization is sensitive to XPO1 inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…The nuclear architecture of cancer cell nuclei is unique. These nuclei undergo dynamic structural aberrations that include changes in their 3D organization of telomeres, chromosomes and chromosome orientation (Mai, ; Gadji et al, ; Righolt et al, ; Martin et al, ; Schmälter et al, ). This study demonstrates that the tumor cell‐specific 3D nuclear telomere organization is sensitive to XPO1 inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Not much is known about the chromosomal orientation in normal and cancer cells. Multicolor‐banding approaches enabled a study of chromosome 11 orientation in normal mouse lymphocytes and in mouse plasmacytoma, compared to control cells . Normal mouse lymphocytes showed three common patterns of orientation, whereas significant differences in the orientation patterns of chromosome 11 were seen between plasmacytoma and control cells of the same mouse strain.…”
Section: The 3d Nucleus In Cancer Cells: Where We Are Today and Wherementioning
confidence: 99%
“…Schmälter et al studied mouse chromosome 11 in lymphocytes of [T38HxBALB/c]N mice with a reciprocal translocation between chromosome X and 11 (T38HT(X;11)) exhibiting a long chromosome T(11;X) and a short chromosome T(X;11) and in fast‐onset plasmacytomas (PCTs) induced in the same strain. They determined the 3D orientation of chromosome 11 using a mouse chromosome 11 specific multicolor banding probe.…”
Section: The 3d Nucleus In Cancer Cells: Where We Are Today and Wherementioning
confidence: 99%
“…Recent quantitative measurements of the three-dimensional (3D) genome structure of normal vs. tumor cell nuclei have indicated that these differences lie in the way the genome is organized. Using centromeres, telomeres, chromosomes, and DNA as tools to measure the 3D organization order, distinct changes can be identified and quantitated (RIGHOLT et al, 2014;SCHMÄLTER et al, 2015;VERMOLEN et al, 2005;YU et al, 2019). These studies have shown that the genome structure can serve as an architectural biomarker of cancer stage and aggressiveness (BABU;FULLWOOD, 2015;GADJI et al, 2010;RANGEL-POZZO et al, 2021a).…”
Section: Genomic Instabilitymentioning
confidence: 99%